2013
DOI: 10.1002/chem.201301081
|View full text |Cite
|
Sign up to set email alerts
|

A Designed 5‐Fluorouracil‐Based Bridged Silsesquioxane as an Autonomous Acid‐Triggered Drug‐Delivery System

Abstract: Two new prodrugs, bearing two and three 5-fluorouracil (5-FU) units, respectively, have been synthesized and were shown to efficiently treat human breast cancer cells. In addition to 5-FU, they were intended to form complexes through H-bonds to an organo-bridged silane prior to hydrolysis-condensation through sol-gel processes to construct acid-responsive bridged silsesquioxanes (BS). Whereas 5-FU itself and the prodrug bearing two 5-FU units completely leached out from the corresponding materials, the prodrug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…As drug candidates, we chose for the pore-blocker a commonly used anticancer drug, 5-fluorouracil (5-FU), which exhibits complementary molecular recognition properties to Stalk. Previously, 23 we have demonstrated that a derivative such as Cap (Fig. 1) with a three-fold H-bonding pattern favours stable complexation at neutral pH in bulk hybrid silica materials.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…As drug candidates, we chose for the pore-blocker a commonly used anticancer drug, 5-fluorouracil (5-FU), which exhibits complementary molecular recognition properties to Stalk. Previously, 23 we have demonstrated that a derivative such as Cap (Fig. 1) with a three-fold H-bonding pattern favours stable complexation at neutral pH in bulk hybrid silica materials.…”
Section: Introductionmentioning
confidence: 76%
“…In contrast, the complex begins to dissociate at lower pH after triazine unit protonation, leading to the breakdown of H-bonds initially involved in stabilization of the capping complex, thus promoting removal of Cap at pH 5.5 and below and its associated release. The biological activity of Cap was previously evaluated 23 by cytotoxic assay on MCF-7 human breast cancer cells, showing a relatively high efficiency (43% of breast cancer cell death at 50 mM) for this molecule as an anticancer drug compared with the parent 5-FU (68% of cell death at 50 mM).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, MONs can also act as drug-delivery systems (DDSs). [ 94,205,211,[230][231][232][233][234][235][236][237][238] The organic fragments within the framework can bring tunable hydrophobicity/hydrophilicity as well as specifi c host-guest interactions with guest molecules, showing more advantages and specifi c behaviors regarding encapsulation, delivery, and release of drug molecules compared to MSNs.…”
Section: Mons For Drug/gene Deliverymentioning
confidence: 99%
“…As an oral antitumor agent, the use of 5-FU was deserted in the last decades due to its atypical intestinal absorption that results in irregular plasma levels with marked inter-and intra-individual variations [9]. This is primarily attributed to the mutable activity of HDPD located in the gastrointestinal mucosa [10].…”
Section: Introductionmentioning
confidence: 99%